Analysis of a simplified Steam Turbine governor model for power system stability studies. (February 2019) - Pondini, M.; Signorini, A.; Colla, V.; Barsali, S.
Abstract: The present study describes an analysis performed on a simplified Steam Turbine governor model, which is useful for pre-tuning the machine regulation system. A dynamic model has been implemented in two different simulation tools, namely DigSILENT PowerFactory and Matlab/Simulink, to the aim of verifying the suitability of the latter one for power system stability studies. The proposed work paves the way to the wide range of possibilities connected to the integration of the machine governor model with other simulation blocks of a Combined Cycle Plant, by enabling the opportunity for pre-commissioning of the regulation system together with the analysis of the fulfillment of grid code regulations.